Prediction of right heart failure after left ventricular assist implantation: external validation of the EUROMACS right-sided heart failure risk score. Issue 7 (29th May 2021) - Rivas-Lasarte, Mercedes; Kumar, Salil; Derbala, Mohamed H; Ferrall, Joel; Cefalu, Matthew; Rashid, Syed Muhammad Ibrahim; Joseph, Denny T; Goldstein, Daniel J; Jorde, Ulrich P; Guha, Ashrith; Bhimaraj, Arvind; Suarez, Erik E; et al.
Abstract: Aims: Prediction of right heart failure (RHF) after left ventricular assist device (LVAD) implant remains a challenge. The EUROMACS right-sided heart failure (EUROMACS-RHF) risk score was proposed as a prediction tool for post-LVAD RHF but lacks from large external validation. The aim of our study was to externally validate the score. Methods and results: From January 2007 to December 2017, 878 continuous-flow LVADs were implanted at three tertiary centres. We calculated the EUROMACS-RHF score in 662 patients with complete data. We evaluated its predictive performance for early RHF defined as either (i) need for short- or long-term right-sided circulatory support, (ii) continuous inotropic support for ≥14 days, or (iii) nitric oxide for ≥48 h post-operatively. Right heart failure occurred in 211 patients (32%). When compared with non-RHF patients, pre-operatively they had higher creatinine, bilirubin, right atrial pressure, and lower INTERMACS class ( P < 0.05); length of stay and in-hospital mortality were higher. Area under the ROC curve for RHF prediction of the EUROMACS-RHF score was 0.64 [95% confidence interval (CI) 0.60–0.68]. Reclassification of patients with RHF was significantly better when applying the EUROMACS-RHF risk score on top of previous published scores. Patients in the high-risk category had significantly higher in-hospital and 2-year mortality [hazard ratio: 1.64 (95% CI 1.16–2.32) P = 0.005]. Conclusion: In an external cohort, the EUROMACS-RHF had limited discrimination predicting RHF. The clinical utility of this score remains to be determined. Graphical Abstract: